A obra para violão de Arthur Bosmans: uma análise da brasilidade nos elementos melódicos, rítmicos e harmônicos - Gustavo de Moraes Farias (2015)
Arthur Bosmans was born in Belgium but lived most of his life in Brazil and much of his compositions fits in the profile of the Brazilian nationalist music. Bosmans wrote two works for solo guitar, the suite Brasileiras in 1974 and the Valsa da outra esquina in 1988 and the present work aims to analyze the "Brazilianness" contained in the melodic, rhythmic and harmonic elements of those works. For it was held the harmonic, melodic and rhythmic analysis of the five movements of the suite Brasileiras and the Valsa da outra esquina in order to assess the consistency of genres and dances chosen with the musical elements used by the composer.